2003
DOI: 10.2141/jpsa.40.254
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Semi-purified Pellet Diet on the Chicken Intestinal Villus Histology

Abstract: To establish the basic histological data on intestinal villi in chickens fed a semipurified pellet diet, birds were divided into the following groups : intact control (IC), --d fasting (F), ad libitum refeeding of a formula mash diet (AFM), or force-feeding of a formula pellet diet (FFP) or a semi-purified pellet diet (FSP) for one day after --d fasting. The intestinal histological recovery in these groups was compared with light (LM) and scanning electron microscopy (SEM).The body weight recovery was similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…Our current histological findings show that duodenal and ileal villus height were decreased (P<0.05) in the low-CP group, and duodenal villus area tended to be decreased (P<0.05) in both the low-CP and low-EE groups, while the ileum showed a lower value (P<0.05) in only the low-CP group. Similarly, previous reports in chickens refed unbalanced nutrient compositions have demonstrated that intestinal villi were shorter and narrower than Incharoen et al in chickens refed a nutritionally well-balanced diet (Maneewan and Yamauchi, 2003, 2004. Decreasing values for villus characteristics corresponded with reductions in the villus surface area, enzyme activities such as mucosal lactase and sucrease (Park et al, 1998), lactase and alkaline phosphatase (Zijlstra et al, 1997), total lactase phlorizin hydrolase and mucosal protein concentration (Dudley et al, 1998), and alkaline phosphatase and disacchar idase (López-Pedrosa et al, 1998).…”
Section: Discussionsupporting
confidence: 59%
“…Our current histological findings show that duodenal and ileal villus height were decreased (P<0.05) in the low-CP group, and duodenal villus area tended to be decreased (P<0.05) in both the low-CP and low-EE groups, while the ileum showed a lower value (P<0.05) in only the low-CP group. Similarly, previous reports in chickens refed unbalanced nutrient compositions have demonstrated that intestinal villi were shorter and narrower than Incharoen et al in chickens refed a nutritionally well-balanced diet (Maneewan and Yamauchi, 2003, 2004. Decreasing values for villus characteristics corresponded with reductions in the villus surface area, enzyme activities such as mucosal lactase and sucrease (Park et al, 1998), lactase and alkaline phosphatase (Zijlstra et al, 1997), total lactase phlorizin hydrolase and mucosal protein concentration (Dudley et al, 1998), and alkaline phosphatase and disacchar idase (López-Pedrosa et al, 1998).…”
Section: Discussionsupporting
confidence: 59%
“…The values of the light microscopic parameters tended to recover to the control level after 1 day of refeeding with formula mash and pellet diets but did not recover in the semi‐purified pellet diet group (Maneewan & Yamauchi 2003). However, various sizes of cell clusters and deeper cells at the sites of recently exfoliated cells were observed on the villus tip in addition to dome‐shaped cells in the formula mash and pellet diet groups.…”
Section: Histological Recovery Responses To Particle Size and Nutritimentioning
confidence: 99%
“…Further study is being carried out to find such a component from SCE. Besides, small particle feed ingredient such as semi-purified pellet diet can easily induce hypertrophic intestinal alteration at epithelial level than villus level (Maneewan and Yamauchi, 2003).…”
Section: Discussionmentioning
confidence: 99%